Factors Affecting Cash Holding (Empirical Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period) - Dyah Ratriwulan; Dadang Suhendar; Siti Nuke Nurfatimah (Indonesian Journal Of Business And Economics, 2023)
AbstractThe purpose of this study is to provide empirical evidence on the Effect of Investment Opportunity Set Ì§ Cash Conversion Cycle, Asset Growth, Net Working Capital and Company Size on Cash Holding. The population in this study was 83 companies with sampling techniques used were the slovin method and quota sampling. The sample used in this study is a Property and Real Estate company that has complete financial statement data for 2017-2022. The sample used in this study was 205 financial statement data or 41 companies. The methods used in this study are descriptive method and verificative method. The data analysis technique in this study uses panel data regression analysis. The results of simultaneous tests show that the variables investment opportunity set Ì§ cash conversion cycle, asset growth, net working capital and company size together affect Cash Holding.Â  Based on the partial test results, the variables investment opportunity set Ì§ cash conversion cycle, asset growth, net working capital and firm size partially have a significant positive effect on cash holding.Keywords: Cash holding, Investment Opportunity Set, Cash Conversion Cycle, Asset Growth, Net Working Capital, Firm Size